Modelling the impact of solvency capital on the efficiency of islamic insurance (takaful) companies in GCC countries - Asafa, Dauda Adeyinka (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2016)
The introduction of minimum capital adequacy and other solvency related regulations by insurance sector's supervisors to protect the Takaful industry in the Gulf Cooperative Council countries (GCC) against adverse consequences of insolvency and bankruptcy has attracted reactions from the industry's stakeholders. While the intent may be commendable, concerns are raised among the stakeholders that compliance with this regulation may impede optimal resource utilization and by extension, their efficiency. This concern is investigated by modelling the impact of solvency capital on the efficiency of Takaful firms operating in the GCC region. A non-parametric mathematical programming technique DEA (data envelopment analysis) with RAM (range adjustment measure) is utilized to analyse the efficiency of selected 80 Takaful companies domicile in the region over the 4-year period from 2009 to 2012. In the analyses, the 'solvency condition' is modelled as a constraint to be satisfied by the management while improving on the efficiency. The cross-sectional analyses produce efficiency scores for the periods under investigation. The efficiency scores produced is subsequently subjected to diagnostic test to determine the statistical significant impact of 'solvency constraints' on efficiency. The result reveals that considerations from the management and regulators are critical in maintaining appropriate solvency condition. Furthermore, the adjustment behaviours to solvency constraints (regulations) at different periods also reflect these considerations. Supplementary statistical test is conducted on each of the three identified independent grouping variables namely, ownership types (i.e. foreign owned vis-a-vis domestic owned Takaful firms), the firm size categories (i.e. large-asset and small-asset size) and cross-country comparison. First, result shows the statistical significant effect of firm-size categories in moderating the relationship between 'solvency constraints' and efficiency in three years (2009-2011). Next, the ownership type grouping shows evidence of interactive effect on the relationship between 'solvency constraints' and efficiency in two periods (2010 and 2012). Third, the cross-country comparisons show no evidence of distinctions in the efficiency across the countries. However, evidence of difference in the distribution of efficiency scores across the countries is shown in 2009 reflecting the Takaful industry's situation in that year. Finally, the latent growth curve modelling is applied to determine the pattern as well as average growth rate of efficiency of Takaful firms over the 4-year period specified in our research and also to test the predictive power (or the effect) of the independent grouping variables. The result indicates that the efficiency of Takaful companies changes over the years and the pattern of trajectory depends on the solvency condition in that period. Moreover, only ownership type out of the three independent grouping variables considered produce evidence of strong predictive power as indicated in the nested model comparison.